Ênfase em políticas sociais como indício de ideologia partidária: uma análise dos programas de governo de PT e PSDB nas eleições de 2002 e 2006 - Vizoná, Amanda (2014)
In a context wich parties new dynamics, goals and articulations are object of analysis, this paper means to analyse the transformation in one of the most fundamental element of the political parties: it's ideological preferencies. Through the operationalization of a new variable called "emphasis on social politics", which uses the concepts of "left and right", this paper measures the ideologial preferencies by analysing the PT's and PSDB's 2002 and 2006 manifestoes. The main objective of this paper ir to test the operationalization of the method of analyse in the brazilian context through the hypothesis that the social politics were the main object in those two elections. Assuming that social politics were the main demands of the public in general, this theme may be also the main element that defines if a party is in the left side of the political spectre or in the right side of it.